Slovenia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in the Republic of Slovenia during 1990-97. Output began to recover in 1993, and by 1996, Slovenia's GDP was back to its pre-independence level. Domestic demand was the main driving force, while the growth of exports fluctuated in line with the business cycle in Western Europe and changes in competitiveness. A strong external contribution brought the GDP growth rate to a peak of 5.3 percent in 1994 but it subsequently slowed, reaching 3.1 percent in 1996. GDP growth picked up again in 1997.